PERAN GURU BERLATARBELAKANG PENDIDIKAN BERBEDA DALAM PERKEMBANGAN MOTIVASI BELAJAR SISWA - Zuhri Fahruddin (Jurnal Asy-Syukriyyah, 2021)
Abstract: The learning carried out by the teacher in the classroom must develop the quality of learning, one of which is learning motivation, students who are not passionate about learning are not optimal and of high quality, from this goal the reality is still far from expectations, many students are not aware of the importance of studying seriously, there is no passion study, there is no fun in the study room. The sampling technique used is Census Sample (Sample Saturated), while criterion-based selection is used when conducting qualitative research, 30 students as primary data sources, two teachers as secondary data sources. Data collection techniques using in-depth interviews, observation, documentation and questionnaires, while data analysis by reducing data, presenting data, drawing conclusions and verification by means of research stages I and II students and teachers with a Da'wah educational background, stage III and IV student informants and teachers with PAI educational background.